The use of the Traditional 'Bakiak Panjang' Games as Media for Reducing Aggressive Behavior of Junior High School Students - Zuhara, Evi; Ubat, Mila Mardewi (IKIP Siliwangi, 2024)
The phenomenon of aggressive behavior still often occurs among teenagers and is included in discriminatory acts that are contrary to school and community norms. Aggressiveness can be manifested in the form of words or physical actions aimed at hurting other people. This research aims to find out how the use of the traditional bakiak panjang games reduces aggressive behavior in junior high school students. The research sample consisted of 12 students selected through a pretest using the purposive sampling method. Data was collected through a Likert scale questionnaire which measures students' level of aggressiveness. This questionnaire was distributed to class VII Babul Maghfirah students and the results were analyzed. The research results show that the calculated t value of 7.750 is higher than the t table value of 1.795, (7.750 > 1.795). This shows a decrease in the level of students' aggressive behavior. Therefore the alternative hypothesis (Ha) is accepted while the null hypothesis (Ho) is rejected. In conclusion, the implementation of the traditional bakiak panjang games can help reduce aggressive behavior in students. This research can be a reference for further research regarding the use of the bakiak panjang games as a medium to reduce students' aggressive behavior.